A word from our Editor-in-Chief: Banca Transilvania S.A (Nonconventional Technologies Review, 2020)
Banca Transilvania (BT) is the largest financial group in Romania, in terms of assets and its mission is to support the development of the business environment, through innovative products and services, offered with professionalism.